Tectonic trigger to the first major extinction of the Phanerozoic:the early Cambrian Sinsk event - Myrow, Paul M.; Goodge, John W.; Brock, Glenn A.; Betts, Marissa J.; Park, Tae Yoon S.; Hughes, Nigel C.; Gaines, Robert R. (Science Advances, 2024)
The Cambrian explosion, one of the most consequential biological revolutions in Earth history, occurred in two phases separated by the Sinsk event, the first major extinction of the Phanerozoic. Trilobite fossil data show that Series 2 strata in the Ross Orogen, Antarctica, and Delamerian Orogen, Australia, record nearly identical and synchronous tectono-sedimentary shifts marking the Sinsk event. These resulted from an abrupt pulse of contractional supracrustal deformation on both continents during the Pararaia janeae trilobite Zone. The Sinsk event extinction was triggered by initial Ross/Delamerian supracrustal contraction along the edge of Gondwana, which caused a cascading series of geodynamic, paleoenvironmental, and biotic changes, including (i) loss of shallow marine carbonate habitats along the Gondwanan margin; (ii) tectonic transformation to extensional tectonics within the Gondwanan interior; (iii) extrusion of the Kalkarindji large igneous province; (iv) release of large volumes of volcanic gasses; and (v) rapid climatic change, including incursions of marine anoxic waters and collapse of shallow marine ecosystems.